Veiga Simão e a democratização do ensino: um ideal em educação - Monteiro, Luis Filipe Barata (1980)
The purpose of this study is to present the analysis of the democratization of schools in the Portuguese educational system. This theme, however, could - and should - not be treated without relating it to the corresponding historical and political processes. Actually, the focused period is one of instability and transition. This explains the more detailed treatment given certain aspects conditioning and circumscribing alI political action in Portugal in the yeas before the 1974 revolution. The democratization of schools in Portual attracts curiosity and is the object of study. Considered a lapse. a hiatus or a parentheses in the Portuguese educational processo part of it is a little of alI this. But not alI. This study intends to show what should be thought of it.